A Cycle-Accurate Simulation Platform for NPU-DRAM Integrated Systems - Park, Hyemin; Kim, Boyeal; Lee, Suhong; Lee, Hyuk Jae; Lee, Hyokeun (Digest of Technical Papers - IEEE International Conference on Consumer Electronics, 2025)
The ever-increasing accuracy of artificial neural networks facilitates various applications in consumer electronic devices. Furthermore, neural processing units (NPUs) enable the real-time processing of neural networks by leveraging domain-specific hardware structures along with considerable on-chip buffers. Unfortunately, the data movement between NPU and off-chip memory (e.g., DRAM) can no longer be ignored; hence, it is necessary to accurately take the performance effect of off-chip memory into consideration, particularly at the architectural-level simulation. In this paper, we propose a configurable, cycle-accurate NPU simulation infrastructure that considers not only the latency effect as in the analytical modeling but also the memory bandwidth utilization. Our simulator reveals that the accurate simulation of off-chip memory captures higher latency compared to analytical modeling. Specifically, it demonstrates the total execution time increases of 19.2%, 2.8%, and 16.2% in ResNet-50, YOLOv3, and BERT, respectively.
Keywords: Consumer electronic devices; Cycle-accurate simulation; Integrated systems; Neural processing unit; Neural-networks; Neural-processing; Off-chip memory; Processing units; Realtime processing; Simulation platform; cycle-accurate simulation; DRAM; NPU